LIDOCAINE -AN OLD DRUG FOR NEW INDICATION (International Journal of Pharmaceutical Sciences and Drug Research, 2013)
Lidocaine, a known local anaesthetic agent has been demonstrated to possess significant efficacy in managing asthma due to its anti inflammatory and direct spasmolytic actions. Various clinical studies have been conducted to assess the role of Lidocaine in asthma management with convincing results showing reduction in steroid dose or discontinuation of steroid therapy associated with improvement in quality of life, marking this old drug as a novel efficacious, fast and safe addition in armamentarium of anti asthma drugs. Inhaled Lidocaine when given alone causes biphasic effect on bronchi with initial bronchoconstriction followed by bronchodilatation. Treatment with combination inhalers, containing Lidocaine and a long-acting β2- agonist seems the safer and more reliable alternative to minimise adverse effects of initial reflex bronchoconstriction caused by inhaled Lidocaine. This review elucidates the available evidence on efficacy and safety of inhaled Lidocaine after analyzing various clinical studies. Searches of pubmed, Cochrane database, Medscape, Google and clinicaltrial.org were made for terms like Lidocaine and bronchial asthma.